ON UNIVERSITY CORPORATE CULTURE DEVELOPMENT WITHIN THE FRAME OF QUALITY MANAGEMENT SYSTEM - Inga Grigoryevna Sagiryan; Vera Vasilyevna Boguslavskaya; Elena Pavlovna Chubova; Manana Giviyevna Komakhidze (Advanced Engineering Research)
The problem on the corporate culture development needed to achieve the strategic and social goals in the higher educational institution is considered. The corporate culture development within the frame of the quality management system (QMS) building is one of the optimal solution approaches to the problem. The key element of the effective university operation is the capability to meet instantly the customer requirements. For that, it is necessary to develop Policy, Mission, and Goals in QMS, as well as principles, values, and traditions which are part and parcel of the corporate culture. Both internal and external strategic development plans, and the basic functions of the educational community corporate culture are analyzed. The value system and the construction principles of the corporate culture are considered.